Pengaruh Substitusi Tepung Beras Dan Penambahan Puree Wortel Terhadap Tingkat Kesukaan Kue Onde-Onde Ketawa - Enrico Putera Subagja; Asrul Bahar; Any Sutiadiningsih; Lucia Tri Pangesthi (Universitas Maritim AMNI Semarang, 2023)
Onde-onde ketawa cookies with substitution of rice flour and addition of carrot puree is one of the innovations in making dry cakes made from wheat flour with substitution of rice flour and addition of carrot puree. The aim of this research is to find out; 1) the effect of the interaction between the substitution of rice flour and the addition of carrot puree on the level of liking for onde-onde ketawa cake; 2) the effect of rice flour substitution and the addition of carrot puree on the level of liking for onde-onde ketawa cake; 3) the effect of adding carrot puree on the level of liking for onde-onde ketawa cake; 4) the composition of the onde-onde ketawa cake with the substitution of rice flour with the addition of carrot puree is the most preferred. The research method used is an experimental type of research with the substitution of 10%, 20% and 30% rice flour and the addition of 5% and 10% carrot puree. The liking test was carried out on 50 untrained panelists using a questionnaire as a research instrument. The data obtained was then analyzed using the double ANOVA test and the Duncan test as further tests. The results of this research show that; 1) The interaction between the substitution of rice flour and the addition of carrot puree has a significant influence on the level of liking for onde-onde ketawa cakes. 2) vi Substitution of rice flour has an effect on the level of liking for onde-onde ketawa cakes; 3) The addition of carrot puree has an effect on the level of liking of onde-onde ketawa cake. 4) Substitution of 10% rice flour and addition of 10% carrot puree produces the most preferred characteristics of onde-onde ketawa cake.